2020
DOI: 10.1159/000507501
|View full text |Cite
|
Sign up to set email alerts
|

Magnification Effect of Foveal Avascular Zone Measurement Using Optical Coherence Tomography Angiography

Abstract: The aim of this study was to evaluate the foveal avascular zone (FAZ) of healthy subjects and examine the magnification effect. Methods: A total of 33 healthy volunteers were enrolled and all subjects were eligible for analysis. Optical coherence tomography angiography (OCTA) examination scanned 3 × 3 mm of the macular area. The FAZ area was measured on the superficial OCTA en face image with and without correction by axial length. The relationship between changes in the FAZ area after correction with the axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…These regional measurements of the choroidal thickness were adjusted for ocular transversal magnification associated with changes in the axial length of the eye. 55,56 Inter-subject variations in the position and size of the optic nerve head (that confounds the measurements of the nasal choroidal thickness) were accounted for by removing the thickness data across the area corresponding to the largest optic nerve head amongst subjects from all horizontal B-scans. To reduce the error in measurements of the choroidal thickness associated with increased retinal curvature in the periphery and localised changes in the CSI (e.g., in the area surrounding the optic nerve head and insertion point of the posterior ciliary vessels), the choroidal thickness was calculated using the Laplace mathematical method with a custom-written programme, 57 consistent with previous studies that have utilised this thickness metric for measurements in the anterior and posterior ocular tissues.…”
Section: Choroidal Thicknessmentioning
confidence: 99%
“…These regional measurements of the choroidal thickness were adjusted for ocular transversal magnification associated with changes in the axial length of the eye. 55,56 Inter-subject variations in the position and size of the optic nerve head (that confounds the measurements of the nasal choroidal thickness) were accounted for by removing the thickness data across the area corresponding to the largest optic nerve head amongst subjects from all horizontal B-scans. To reduce the error in measurements of the choroidal thickness associated with increased retinal curvature in the periphery and localised changes in the CSI (e.g., in the area surrounding the optic nerve head and insertion point of the posterior ciliary vessels), the choroidal thickness was calculated using the Laplace mathematical method with a custom-written programme, 57 consistent with previous studies that have utilised this thickness metric for measurements in the anterior and posterior ocular tissues.…”
Section: Choroidal Thicknessmentioning
confidence: 99%
“…The magnification effect should be considered when evaluating FAZ area in myopic eyes (Suda et al. 2020). In our study, a FAZ size correction was not done, because none of the included eye was highly myopic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Suda et al suggested that AL correlation in image analysis is important when the FAZ area is measured using OCTA. 21 Linderman et al reported that the FAZ area had a negative correlation with the AL when the AL correction in image analysis was not considered; however, this correlation existed when the AL correction was considered. 22 In our study, the FAZ area of the DRL showed a weak negative correlation with the AL.…”
Section: Discussionmentioning
confidence: 99%